Photodynamic therapy with upconversion nanoparticles - Güleryüz, Burcu. (Thesis (Ph.D.)-Bogazici University. Institute of Biomedical Engineering, 2022., 2022)
Photodynamic therapy (PDT) is an alternative approach to conventional meth ods (i e. chemotherapy and radiotherapy) that can be utilized to treat various cancers with less side effects. However, PDT has some restrictions such as photosensitizers delivery and light penetration depth. It was realized that these problems can be over come with the improvements in nanotechnology; and today, many researchers have been initiated to study on PDT with various combinations of photosensitizers-nanoparticles. Recently, upconversion nanoparticles (UCNP) have revealed promising results with different surface designs. UCNP’s unique anti-Stokes conversion capabilities en able the transmission of near-infrared (NIR) to visible light, providing a solution to the light penetration depth problem of traditional PDT. Since they have organic struc ture, UCNP do not show high biotoxicity and additional surface modifications allow photosensitizers delivery to the desired region of a body. In this study, Yb/Er doped UCNP was synthesized and coated with porous sil ica to merge MC540 and ZnPc photosensitizers. In order to prevent photosensitizers leakage over time and optically strengthen the nanoparticles for PDT activity, silica surface was conjugated with APTES-gold nanoparticles. Experiments on prostate can cer cells with this novel design revealed two notable results: (I) nanoplatforms exerted high biocompatibility that even 2 mg/ml concentration could be employed, and (II) the viability of cells was successfully reduced up to 35%. Furthermore, PDT effect of 3-4 nm sized gold nanoparticles on cells was detected for the first time.|Keywords : Photodynamic Therapy, Upconversion Nanoparticles, Mesoporous Silica, Gold Nanoparticles, MC540 and ZnPc Photosensitizers, Prostate Cancer.
Keywords: Photochemotherapy.; Nanoparticles.